Status and Changes in Composition of Agricultural Household’s Income in India (Indian Journal of Extension Education, 2022)
The study used the NSSO’s Situation Assessment Survey from 2012-13 and 2018-19 to determine the current status and changes in the composition of agricultural household income. During the agricultural years 2012-13 and 2018-19, an agricultural household’s total nominal farm income increased at an annual rate of 9.61 per cent, while real income increased at a rate of 3.42 per cent. Assuming the projected growth trends in nominal and real income continue, the nominal income of agricultural households will take 7.5 years to double at All India levels, while the real income will take 21 years. The income composition of an agricultural household changed throughout the same period. The average annual percentage change in income from wages and salaries (10.37%) and from animal sources (6.14%) grew positively throughout the period, whereas crop (-1.25%) and non-farm business (-0.94%) grew negatively. 12 per cent increase in the share of wages and salaries in overall income was discovered and a corresponding reduction in crop income. In the agricultural year 2018-19, Rajasthan had the largest diversity in income sources (SID=0.43), and Andhra Pradesh had the lowest (SID=0.25), while All India had (SID=0.35). The result indicates that agricultural households are shifting their dependency for livelihood from crop income towards wages and salaries.